Lack of Association between TLR4 Genetic Polymorphisms and Diabetic Nephropathy in a Chinese Population. (23rd March 2014) - Peng, Danfeng; Wang, Jie; Pan, Jiemin; Zhang, Rong; Tang, Shanshan; Jiang, Feng; Chen, Miao; Yan, Jing; Sun, Xue; Wang, Tao; Wang, Shiyun; Bao, Yuqian; et al.
Abstract : Objective . Toll-like receptor 4 (TLR4) plays a central role in innate immunity. Activation of innate immune response and subsequent chronic low-grade inflammation are thought to be involved in the pathogenesis of diabetic nephropathy. In this study, we aimed to investigate whether TLR4 variants are associated with diabetic nephropathy in the Chinese population. Methods . Seven tagging single nucleotide polymorphisms (SNPs) of TLR4 based on HapMap Chinese data were genotyped in 1, 455 Chinese type 2 diabetic patients. Of these patients, 622 were diagnosed with diabetic nephropathy and 833 were patients with diabetes for over 5 years but without diabetic nephropathy. Results . None of the SNPs and haplotypes showed significant association to diabetic nephropathy in our study. No association between the SNPs and quantitative traits was observed either. Conclusion . We concluded that common variants within TLR4 genes were not associated with diabetic nephropathy in the Chinese type 2 diabetes patients.